Design-Based Learning Model and Senior Secondary Students’ Learning Achievement in Solid Geometry - Wonu, Nduka; Arokoyu, Abosede Ajoke (European Scientific Journal, ESJ, 2016)
This study is an exploration of the effectiveness of Design-Based Learning (DBL) model in the improvement of senior secondary students’ achievement in solid geometry in Emohua Local Government Area of Rivers State. The quasi-experimental design was adopted. A sample of 59 Senior Secondary School I (SSSI) students took part in the study. Solid Geometry Achievement Test (SGAT) was the instrument used for data collection. The Kuder-Richardson KR-21 method was used to establish the reliability of SGAT to obtain an index of 0.84. Two research questions and two null hypotheses guided the study. The research questions were answered using mean and standard deviation while the hypotheses were tested using Analysis of Covariance (ANCOVA) at .05 level of significance. The findings established that DBL model was superior to Problem-based Learning (PbL) model in advancing the learning achievement of students in solid geometry. The students of both groups improved in learning over time with higher learning gain among students in the experimental group. The male and the female students in the experimental group outperformed their counterparts in the control group over SGAT scores. The male and the female students taught using the DBL and PbL respectively did not significantly differ over SGAT scores. It was recommended among others that mathematics teacher should apply the DBL in teaching solid geometry in the senior secondary schools in Nigeria because when effectively utilized, this instructional model is capable of advancing the learning achievement of students in mathematics irrespective of their locations and gender